Islamic Social Finance In Addressing Poverty Reduction And Economic Growth: Using Structural Equation Modeling - Tijjani Muhammad; Fahd Al-Shaghdar; Shariff Muhammad Ibrahim (Usim Press, 2024)
Journal of Muamalat and Islamic Finance Research (JMIFR) Volume 20 No.2 Page (179-191)